GSK-3β Overexpression Alters the Dendritic Spines of Developmentally Generated Granule Neurons in the Mouse Hippocampal Dentate Gyrus - Pallas-Bazarra, Noemí; Kastanauskaite, Asta; Avila, Jesús; DeFelipe, Javier; Llorens-Martín, María (Frontiers in Neuroanatomy, 2017)
The dentate gyrus (DG) plays a crucial role in hippocampal-related memory. The most abundant cellular type in the DG, namely granule neurons, are developmentally generated around postnatal day P6 in mice. Moreover, a unique feature of the DG is the occurrence of adult hippocampal neurogenesis, a process that gives rise to newborn granule neurons throughout life. Adult-born and developmentally generated granule neurons share some maturational aspects but differ in others, such as in their positioning within the granule cell layer. Adult hippocampal neurogenesis encompasses a series of plastic changes that modify the function of the hippocampal trisynaptic network. In this regard, it is known that glycogen synthase kinase 3β (GSK-3β) regulates both synaptic plasticity and memory. By using a transgenic mouse overexpressing GSK-3β in hippocampal neurons, we previously demonstrated that the overexpression of this kinase has deleterious effects on the maturation of newborn granule neurons. In the present study, we addressed the effects of GSK-3β overexpression on the morphology and number of dendritic spines of developmentally generated granule neurons. To this end, we performed intracellular injections of Lucifer Yellow in developmentally generated granule neurons of wild-type and GSK-3β-overexpressing mice and analyzed the number and morphologies of dendritic spines (namely, stubby, thin and mushroom). GSK-3β overexpression led to a general reduction in the number of dendritic spines. In addition, it caused a slight reduction in the percentage, head diameter and length of thin spines, whereas the head diameter of mushroom spines was increased.